Hubungan Motivasi Belajar Siswa dengan Persepsi Siswa dalam Berprestasi [The Relationship between Students' Motivation and Students' Perceptions of Achievement] - Rosyeline Nesac Djuarsa; Imanuel Adhitya Wulanata; Dylmoon Hidayat (Polyglot, 2017)
Learning achievement is influenced by many factors, such as teaching methods, the means and facilities available, the environment and student motivation to learn. One of the problems found in the school was weak student motivation for learning. Which in the end has an impact on the perception of students in achieving good results. The purpose of this research is to know if there is any correlation between the students’ learning motivation and students’ perception of learning achievement and what is the correlation of the students’ learning motivation and students’ perception of learning achievement. This research used a quantitative approach with a sample size of 30 students. Data were collected using a questionnaire. The validity of this instrument construction was obtained from three expert judgments. The empirical validity of this instrument was calculated by the formula of Rank Spearman. The variables concerning student learning motivation consisted of 18 items and the variables indicating student perception of learning achievement consisted of 8 items. Reliability is measured with Cronbach Alpha. The Alpha value obtained for the variables of student learning motivation was 0.865 and the Alpha value of the variable students’ perception of learning achievement is 0.781. Data were analyzed using the Spearman rank correlation (Rho-Spearman) and significance test connection with the distribution of t test at a significance level of 5%. The results of this research showed a significant positive correlation between students’ learning motivation and student perception of learning achievement (r = 0.612, sig= 0,000. That means that the higher the student learning motivation the stronger the student perception of learning achievement.BAHASA INDONESIA ABSTRAK: Prestasi belajar dipengaruhi banyak faktor, misalnya metode guru dalam mengajar, sarana dan fasilitas yang tersedia, lingkungan dan motivasi siswa dalam belajar. Salah satu masalah yang ditemukan di sekolah adalah lemahnya motivasi belajar yang dimiliki siswa yang akhirnya berdampak kepada persepsi siswa dalam berprestasi. Tujuan penelitian ini adalah untuk mengetahui adakah hubungan motivasi belajar siswa dengan persepsi siswa dalam berprestasi  dan bagaimanakah hubungan motivasi belajar siswa dengan persepsi siswa dalam berprestasi. Penelitian ini menggunakan pendekatan kuantitatif dengan jumlah sampel sebanyak 30 siswa. Data dikumpulkan dengan menggunakan kuesioner. Validitas konstruksi instrumen diperoleh dari 3 expert judgment (ahli). Validitas empirik instrumen dihitung dengan rumus Rank Spearman, variabel motivasi belajar siswa terdiri dari 18 item dan variabel persepsi siswa dalam berprestasi terdiri dari 8 item. Reliabilitas diukur dengan Alpha Cronbach, diperoleh nilai Alpha variabel  motivasi belajar siswa adalah 0,865 dan nilai Alpha variabel persepsi siswa dalam berprestasi adalah 0,781. Data dianalisis dengan menggunakan korelasi peringkat spearman (Rho-Spearman) dan uji signifikansi hubungan dengan uji distribusi t pada taraf signifikansi 5%. Hasil analisis ini menunjukkan adanya hubungan yang positif signifikan antara motivasi belajar siswa dengan persepsi siswa dalam berprestasi (r = 0,612, sig = 0,000. Artinya semakin baik atau tinggi motivasi belajar siswa maka akan semakin besar dan kuat juga persepsi siswa untuk meraih prestasi.